IMPROVING THE METHODOLOGY FOR DEVELOPING EDUCATIONAL LEXICAL COMPETENCE IN PRE-SERVICE ENGLISH LANGUAGE TEACHERS - Alixanova Dilbar (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the theoretical and practical aspects of improving the methodology for developing educational lexical competence in pre-service English language teachers. The structural components of lexical competence, the factors influencing its formation, and effective teaching methods based on modern methodological approaches are analyzed. The results indicate that systematic development of lexical competence is a key factor in enhancing the professional training of future English language teachers.